Income tax exemption as a regional state aid in special economic zones and its impact upon development of Polish districts - Adam A. Ambroziak (Institute of Economic Research (IER), 2015)
Special Economic Zones (SEZs) were established to attract entrepreneurs to invest in Polish regions in order to increase their social and economic development. One of the most important incentives offered in SEZs is state aid in the form of an income tax exemption. The objective of this paper is to verify if the intensity of regional state aid granted to entrepreneurs in SEZs has had a positive impact on the social and economic development of Polish poviats (a poviat is an administrative district). The public aid was received by beneficiaries when they made some profits and, instead of investing, used a tax allowance to decrease their tax base. However, part of the positive outcome of economic activities envisioned in SEZs should be the development of existing businesses and the emergence of start-ups, as well as the improved attractiveness of the region and the inflow of new investors (which should be manifested by an increase in the gross value of fixed assets per entrepreneur and a decrease in the unemployment rate at poviat level). The conducted research allowed for the conclusion that regional state aid in SEZs in the form of an income tax exemption was of a relative higher importance to the poorest regions (higher share in the amount of regional state aid), while its significance was much lower in better developed areas in Poland (lower share in the amount of regional state aid). The year-to-year study showed no relation between state aid granted in SEZs and an increase in GVFA per company or a decrease in the unemployment rate. However on the basis of analysis of the cumulated value of state aid in SEZs for the whole period from 2005 to 2013, we can say that regional state aid in the form of an income tax exemption in SEZs had a positive influence mainly in poviats located in the poorest voivodeships.
Keywords: H25; H32; R11; R58; 330; regional state aid; special economic zones; regional development; poviats in Poland; public support